ALIRAN JABARIYAH DAN IMPLIKASINYA DALAM PEMBANGUNAN KARAKTER SOSIAL - Arifan Ananda; Nunu Burhanuddin (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
This article delves into the realm of Islamic thought, specifically exploring the domain of Kalam, often referred to as the science of theological discourse. Kalam, literally meaning "words," involves the intricate debates among Islamic theologians who skillfully wield words to defend their beliefs. It encompasses the study of Islamic theology or Ushuluddin, focusing on the foundational teachings of the religion. The pursuit of theological knowledge provides individuals with fundamental convictions that are resilient against easy wavering. As the narrative unfolds, it addresses the emergence of differences within the Islamic community. Initially rooted in political realms, these differences gradually evolve into theological issues over time. The theological variances among Muslims manifest both practically and theoretically. Theoretical distinctions surface through debates on various issues, with philosophical aspects taking precedence over matters such as the oneness of Allah, faith in prophets, angels, the Day of Judgment, and the teachings of the Prophet that are deemed beyond dispute. This study directs attention to the Jabariyah theological school as a focal point. The term "Jabariyah" linguistically stems from "jabara," signifying coercion. In theological terms, Jabariyah rejects human agency, attributing all actions to Allah. It posits that humans act out of compulsion, emphasizing the absolute authority and will of Allah. The theological discourse of Jabariyah revolves around the interplay between human actions and divine acts, pondering the extent to which humans are subject to the absolute will and power of Allah. The research methodology employed in this article is literature review, gathering insights from various books, articles, and journals. A critical descriptive approach is adopted, prioritizing the analysis of data sources. The investigation draws from articles and journals authored by education experts with relevant experience. The article elucidates the unclear origins of Jabariyah, with divergent views on its inception. Scholars posit its emergence during the era of the companions of Prophet Muhammad and the Umayyad Caliphate, intertwined with discussions on Qadar (predestination) and human agency in the face of Allah's absolute power. Others suggest its roots predate Islam, influenced by the challenging environment of the Arabian desert. The implications of Jabariyah's doctrine in shaping social character are explored in the context of contemporary society marked by rapid advancements in science and technology. The article contends that theological teachings must compete with other disciplines in influencing human understanding. It argues that the static nature of Jabariyah fosters a sense of human powerlessness and dependency on the absolute will of Allah, potentially hindering progress. In conclusion, the article reflects on the impact of Jabariyah's doctrine, noting its potential to engender a static mindset and hinder societal progress by emphasizing human dependency on the will of Allah. This theological perspective, seen as a response to the freedom-oriented Qadariyah school, contends that creatures have no capacity to shape their lives but merely fulfill what Allah has decreed.